ANALISIS SISTEM AKUNTANSI PEMERINTAH PUSAT (SAPP) DI KANTOR AKUNTANSI REGIONAL JAKARTA - Titis Wahyuni (Program Pendidikan Vokasi Universitas Indonesia, 2013)
ABSTRACT - This research is intended to describe Central Government Accounting System (SAPP)implemented by the State Financial Accounting Agency (BAKUN) through The Regional Accounting Office(KAR) and the expected outcomes of Central Government Accounting System. In a accounting system, financialstatements generated rely on the accuracy and validity of data input transactions. The accuracy and validity ofthe Government's financial statements generated will depend on the quality of the work done by KARs inmanaging the Government's financial transaction data input.The method usedin this research isby analyzing the problems/obstaclesfaced by KAR Jakarta and alsoanalyzing the process performed by KAR Jakarta during 2000 – 20001. Analysis was performed on cashreceipt transactiondata processingsubsystem (Cash Receipt) and governmentcashexpenditures (CashDisbursement), and general ledger subsystem (General Ledger) used and done by using Analysis CriticalSuccess Factor (CSF), Performance Grid, Proses Modeling, Data Modeling, and Network Modeling. Theresult of this research shows that there are some problems/obstacles faced by KAR in managing data offinancial transactions of the Government. By using these results are then made efforts to repair the runningsystem.Keywords: Central Government Accounting System, Regional Accounting Office, Central AccountingSystem, process modeling, data modeling, critical success factor.